Study of diagnosis and management of ectopic pregnancy - Patel, Seema; Desai, Ajesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Diagnosis of ectopic pregnancy was frequently missed. Aim of the study was to determine the clinical presentation, and treatment associated with ectopic pregnancy. Methods: This is a prospective study which was carried out at Obstetrics and Gynaecology department, GMERS SOLA civil hospital from August 2017 to October 2018. Total 416 patients were admitted during study period out of them 50 patients diagnosed with ectopic pregnancy were enrolled in the study and information was collected and analysed. Results: 80% patients were between the age group of 21-30 years. 56% patients were nulliparous. Amenorrhea (92%) with lower abdominal pain (94%) is the most common presenting symptom. 26% of patients show typical triad of amenorrhea, abdominal pain and bleeding per vagina. UPT and USG were most commonly performed investigations. 96% cases showed UPT positive. 100% USG showed adnexal pathology. Serum beta-hCG was done in 37 patients as an aid for diagnosis and to decide the line of management. Conservative medical management with Injection MTX was done in 4 patients of which 1 patients required laparotomy later on. Surgical management was done in 90% of patients. Laparoscopic management was done in 54% of cases. Conclusions: Early diagnosis and timely intervention in the form of conservative or surgical treatment will help in reducing the morbidity and mortality associated with ectopic pregnancy.